Penal harm and unusual conditions of confinement: Inmate perceptions of ‘hard time’ in jail - Griffin, Marie L. (American journal of criminal justice, 2006)
Despite the increasingly punitive public policies of the past three decades and the concomitant ‘get tough’ rhetoric aimed at reducing prison and jail amenities, little is known about inmates’ perceptions of punishment. Prison and jail administrators often justify their efforts to increase the “pains of imprisonment” for incarcerated offenders on the basis of retribution and deterrence, but these policies appear to be more symbolic than substantive in nature. Using interview data from 232 inmates about to be released from a large county jail renown for its ‘get tough ’ policies, this study examined inmate perceptions of their unusual conditions of confinement. Findings suggest that many of these policies were benign or even counterproductive to the extent that they promoted a defiant response from offenders.